A Systematic Review of the Risks of Motor Vehicle Crashes Associated with Psychiatric Disorders. (April 2023) - Rapoport, Mark J.; Chee, Justin Nathaniel; Prabha, Thadshagini; Dow, Jamie; Gillespie, Ian; Koppel, Sjaan; Charlton, Judith L.; O'Neill, Desmond; Donaghy, Paul C.; Ho, Angela Onkay; Taylor, John-Paul; Tant, Mark
Objective: Psychiatric disorders and their treatments have the potential to adversely impact driving skills. However, it is unclear to what extent this poses a public health risk by increasing the risk of motor vehicle crashes (MVCs). The aim of this systematic review was to synthesize and critically appraise evidence on the risk of MVC for drivers with psychiatric disorders. Method: We conducted a systematic review of the MVC risk associated with psychiatric disorders using seven databases in November 2019. Two reviewers examined each study and extracted data. The National Heart, Lung, and Blood Institute Quality Assessment tools were used to assess each study's quality of evidence. Results: We identified 24 studies that met the inclusion criteria, including eight cohort, 10 case-control, and six cross-sectional designs. Quality assessment ratings were "Good" for four studies, "Fair" for 10, and "Poor" for 10. Self-report or questionnaires were used in place of objective measures of either MVC, psychiatric disorder, or both in 12 studies, and only seven adjusted for driving exposure. Fifteen studies reported an increased risk of MVC associated with psychiatric disorders, and nine did not. There was no category of disorder that was consistently associated with increased MVC risk. Conclusion: The available evidence is mixed, not of high quality, and does not support a blanket restriction on drivers with psychiatric disorder. An individualized approach, as recommended by international guidelines, should continue. Further research should include objective assessments of psychiatric disorders and MVC risk and adjust for driving exposure.